Legal Protection for Carriers of Keris as Cultural Heritage Objects for the Development of Keris Cultural Progress: Analysis of Decision Number 94/pid.sus/2013/PN.Smp - Sjaifurrachman, Sjaifurrachman; Fithry, Abshoril (Journal of Progressive Law and Legal Studies, 2024)
Sumenep is now beginning to reveal its identity to the people of Indonesia, with its new motto "Sumenep City of Keris." This motto is being introduced to the public to introduce the culture of the city. However, it is regrettable that the opportunity for the keris industry in Sumenep Regency cannot contribute positively to the economic welfare of the population there, due to the lack of support from the Sumenep Regency Government in making policies, which is still insufficient. The sensitivity of local governments is currently being tested, especially with the existence of Emergency Law Number 12 of 1951 in Indonesia. After Sumenep City declared itself a city of keris, it is feared that many people will need legal protection if they want to carry heirloom items such as keris in the future. Researchers consider this emergency law to be outdated or obsolete because it no longer fits the current situation and conditions.